“Can I Work Here?”: Employment Barriers for Individuals with Intellectual Disabilities in Greece - Rachanioti, Eleni; Giaouri, Stergiani; Laskaraki, Eleni; Alevriadou, Anastasia (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Research evidence has shown that employment is crucial and purposeful for people with intellectual disabilities, promoting positive effects associated with independent living and social inclusion. Notwithstanding, people with intellectual disabilities find it particularly difficult to accomplish successful employment. They face discrimination, and they are considered to lack work capacity. The extremely marginal position of people with intellectual disabilities in the labor market appears to prevail across national settings. Over the last 35 years, there has been an improvement in the vocational inclusion of individuals with intellectual disabilities in Greece, with the legislation embracing the human rights-based approach to disability. Nevertheless, the challenge of accomplishing full participation and equality in employment for people with intellectual disabilities still remains huge in Greece. Their participation rates in the Greek labour market are significantly lower than in the rest of the European Union. This article illustrates the employment provisions for individuals with intellectual disabilities in Greece. Additionally, it presents the current implemented models of their occupational inclusion while critically discussing the convention’s pursuance on the Rights of Persons with Disabilities in the Greek context.